1999
DOI: 10.1590/s0034-71081999000100008
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of jack bean [Canavalia ensiformis (L.) DC.] canatoxin to plant pathogenic fungi

Abstract: Protein fractions obtained from seeds of the jack bean (Canavalia ensiformis) as well as the amino acid canavanine, present in these seeds, were tested for their capacity to inhibit the growth of the phytopathogenic fungi Macrophomina phaseolina, Colletotrichum gloesporioides, Sclerotium rolfsii and Fusarium oxysporum. We found that most of the proteins examined and also canavanine did not have any effect on the growth of these fungi. On the other hand the toxic protein canatoxin was found to be effective, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Ureases are toxic against filamentous fungi and yeasts [183] . The fungitoxic activity of CNTX was the first reported showing that the protein at 2% concentration caused growth inhibition of the phytopathogenic filamentous fungi Macrophomina phaseolina, Colletotrichum gloesporioides and Sclerotium rolfsii [184] . Becker-Ritt et al, 2007, reported that JBU and the soybean embryo-specific ureases inhibited growth and/or spore germination of seven other species of filamentous fungi at sub-micromolar concentrations and caused damage to cell wall, even after blockage of their ureolytic active sites.…”
Section: Contributions Of Ureases To Plant Defense Against Predators mentioning
confidence: 99%
“…Ureases are toxic against filamentous fungi and yeasts [183] . The fungitoxic activity of CNTX was the first reported showing that the protein at 2% concentration caused growth inhibition of the phytopathogenic filamentous fungi Macrophomina phaseolina, Colletotrichum gloesporioides and Sclerotium rolfsii [184] . Becker-Ritt et al, 2007, reported that JBU and the soybean embryo-specific ureases inhibited growth and/or spore germination of seven other species of filamentous fungi at sub-micromolar concentrations and caused damage to cell wall, even after blockage of their ureolytic active sites.…”
Section: Contributions Of Ureases To Plant Defense Against Predators mentioning
confidence: 99%
“…Table 2 summarizes some of these overlooked biological activities of plant ureases. The main discoveries were made for the jackbean ureases (CNTX and JBU), revealing several interesting properties, such as entomotoxicity [74][75][76][77], fungitoxicity [78,79] and secretory activity [5,80].…”
Section: New Features Of An Old Protein -Activities Unrelated To the mentioning
confidence: 99%
“…Uma das propriedades desse composto está relacionado aos mecanismos de defesa das plantas. Canavalia ensiformes possui diversos metabólitos antinutricionais como a lectina, canavalina A, uréases, inibidores de proteases e canatoxina que em conjugação com os galactomananos têm efeito tóxico no desenvolvimento das larvas de insetos (Oliveira et al 1999a;b). A ausência de sementes com sinais de herbivoria (dados não mostrados) em C. rosea pode indicar a presença de compostos antinutricionais com função antiherbivoria como constatado em Canavalia ensiformes (Oliveira et al 1999a;b) e em outras espécies do Gênero Canavalia (Sridhar & Seena 2006).…”
Section: Resultsunclassified